Hybrid security governance in Africa: rethinking the foundations of security, justice and legitimate public authority. Issue 1 (2nd January 2016) - Bagayoko, Niagale; Hutchful, Eboe; Luckham, Robin
Abstract: This article asks whether the concept of 'hybridity' offers a more convincing account of security governance in Africa than the standard state-focused models. It seeks to clarify the complex intersections between formal and informal, state and non-state security actors, and the varied terrains on which hybridity is constructed, instrumentalised and recalibrated over time. Rather than romanticising informal or 'traditional' institutions, it suggests that they too embed their own power hierarchies, become sites of contestation, and do not work equally well for everyone, least of all for the weak, vulnerable and excluded. Thus the focus is placed upon the real governance of security in hybrid systems, and the patterns of inclusion and exclusion (including gender biases) they reinforce. Finally the paper considers how policy-makers and shapers can work with the grain of hybrid security arrangements to create more legitimate, broadly-based and effective African security governance.